The diversity of freshwater fishes at three tributaries of Tuaran River (Mantaranau River, Tombongon River and Kimaulau River) / Sarah J. Mianus - Mianus, Sarah J. (2013)
Fish collection were made at three tributaries of Tuaran River namely Mantaranau River, Tombongon River and Kimaulau River. All three rivers are located at upper zone and generally have similar characteristics such as shallow, fast flowing water, rocky bottom with high level of dissolved oxygen. These characteristics are similar to the characteristics of an upper stream. The rivers were surrounded by riparian forest and were a part of Tagal System, a local system for river conservation and agro-tourism. Cast nets were used for fish sampling. A total of 10 species of 8 genera belonging to 2 families were collected at all three rivers. 4 similar species were collected at all three rivers. 95.1% of the total individuals caught belongs to Cyprinidae family while the remaining 4.9% belongs to Balitoridae family. Endemic species of Borneo such as the Gastromyzon monticola, Lobocheilus bo, Paracrossochilus acerus and Garra bornensis were also found in the rivers studied. The Gastromyzon species is an important species used as biological indicator for water quality. The economically valuable species such as the Tor species were also found in the rivers studied. Kimaulau River has higher diversity index compared to Mantaranau River and Tombongon River with index of 2.00, 1.66 and 1.20 respectively. The implementation of Tagal System at Tuaran River had contributed to the success of sustaining Tuaran River and conserving its natural inhabitants especially the endemic species.